Penerapan model pembelajaran picture and picture untuk meningkatkan hasil belajar siswa pada mata pelajaran IPA - muthoharoh, Rifa; Wahono, Bevo; Marasabessy, Rosida (Asian Journal Collaboration of Social Environmental and Education, 2024)
This research aims to improve student learning outcomes in science subjects on human digestive organs by using the picture and picture learning model. This research is classroom action research with the research subjects being class V students of MI Tarbiyah Athfal II Kepundungan Banyuwangi consisting of 16 students. Classroom action research in this study consists of two cycles, each cycle consisting of four stages, namely planning, implementation, observation and reflection. The data collection techniques used are observation and learning outcomes tests. Completeness criteria are achieved if classically   obtain a minimum score of 70. Data analysis techniques use qualitative and quantitative data analysis techniques. The research results showed that in cycle I there was an increase in 9 students with a percentage of 56.25%, while in cycle II there was an increase in 13 students with a percentage of 81.25%. Based on these results, it can be concluded that applying the picture and picture learning model can improve student learning outcomes in science subjects on human digestive organs.